PENGARUH MANAJEMEN BIMBINGAN DAN KONSELING TERHADAP MORAL PESERTA DIDIK DI MTS NEGERI 2 KOTA TASIKMALAYA - Nur Halijah, Sabrina (Program Studi Manajemen Pendidikan Islam, 2025)
Guidance and counseling management plays a strategic role in shaping students’ morality at school. This study aims to analyze the influence of guidance and counseling management on students’ morality at MTs Negeri 2 Kota Tasikmalaya. A quantitative correlational approach was employed, with data collected through questionnaires and documentation. The sample involved 55 educators and 55 students, and the data were analyzed using IBM SPSS version 26. The results indicate that guidance and counseling management is at a moderate level (63.6%), while students’ morality is also at a moderate level (74.5%). The coefficient of determination shows a value of 36.6%, meaning that guidance and counseling management contributes significantly to students’ morality, while the remaining percentage is influenced by other factors. The t-test with a significance value of 0.000 < 0.05 further confirms the significant effect. These findings highlight that although guidance and counseling management is not the only factor, it plays a substantial role in fostering morality, and therefore must be strengthened systematically and sustainably.